KOMPOSISI STRUKTUR DAN ESTIMASI CADANGAN KARBON DI PULAU BANGKO-BANGKOANG KABUPATEN PANGKEP - Herawaty, Herawaty; Nasir, Anugrahandini Nasir; Andraini, Dea Ekaputri; Ismail, Ismail (Program Studi Kehutanan Universitas Muslim Maros, 2025)
Mangrove ecosystems play a crucial role in climate change mitigation, particularly in carbon storage. This study was conducted on Bangko-Bangkoang Island, Pangkep District, South Sulawesi, to assess the carbon stock and species composition of mangroves in the area. The aim of this research was to analyze the aboveground biomass and carbon sequestration potential of the mangrove ecosystem. Field data were collected using a systematic sampling technique with a random start, where 20 x 20-meter plots were established. Biomass was calculated using allometric equations, and carbon stock was determined and converted to CO2 equivalent. The results showed that Rhizophora mucronata contributed the largest carbon stock, with 592.91 tons per hectare, equivalent to 2173.99 tons per hectare CO2-eq. Rhizophora stylosa stored 118.89 tons of carbon per hectare, equivalent to 435.94 tons per hectare CO2-eq, while Sonneratia alba stored 14.30 tons of carbon per hectare, equivalent to 52.45 tons per hectare CO2-eq. This study highlights the importance of mangrove conservation as a strategy for climate change mitigation, given its significant capacity for carbon storage and CO2 emission reduction